Effects of spinal anaesthesia related complication and demographic distribution on patient satisfaction following caesarean section - AYSE VAHAPOGLU; ULKU AYGEN TURKMEN; HANDE GUNGOR; OMER FARUK KOSEOGLU (Medicine Science, 2019)
Patient satisfaction is an important issue for patients overall health status and perception. Aim of the present study was to evaluate spinal anaesthesia related complications and other factors related with overall satisfaction level and compare satisfaction levels of patients from 3 different regions of Turkey whom underwent caesarean section (CS) procedure under spinal anesthesia. Satisfaction levels of 285 patients underwent caesarean section under spinal anaesthesia were evaluated at postoperative 1st and 3rd days using a questionnaire form. Also perioperative complications and possible correlations between satisfaction levels were investigated. Patients satisfaction levels were not affected by origins of patients. Most of the patients expressed satisfaction after spinal anaesthesia both at 1st and 3rd days postoperatively (82.1% vs 79.6% respectively). Postoperative pain at surgical site, backache and headache were top 3 factors related with decreased patient satisfaction. Also recurrent spinal puncture attempts, painful puncture attempts, inadequate analgesia, postoperative nausea and vomiting were correlated with decreased satisfaction levels (p [Med-Science 2019; 8(4.000): 941-6]